Regulatory B cells, the key regulator to induce immune tolerance in organ transplantation - Liao, Jinfeng; Yang, Yixin; Li, Jisong; Liu, Zheng; Song, Siyuan; Zeng, Yu; Wang, Yi (Frontiers in Immunology, 2025)
In solid organ transplantation, especially renal transplantation, for the induction of immune tolerance, accumulating evidence has revealed that Regulatory B cells (Breg) play a crucial role in stimulating immune tolerance, alleviating immune responses, and improving graft survival. We describe the heterogeneous nature of Bregs, focusing on their defining surface markers and regulatory functions. Meanwhile, the major cytokine secretion function and the correlation between Breg and Treg or other immune checkpoints to balance the immune responses are addressed. Furthermore, we summarized the intrinsic and extrinsic pathways or costimulatory stimuli for the differentiation from naïve B cells. More importantly, we summarized the progression of the immune tolerance induction role of Breg in solid organ (kidney, liver, heart, lung, and islet) transplantation. This is an up-to-date review from the origin of Breg to the function of Breg in solid organ transplantation and how it induces immune tolerance in both murine models and human solid organ transplantation.